Effect of pregnancy and foetal number on diameter of corpus luteum, maternal progesterone concentration and oxidant/antioxidant balance in ewes - Gür, S; Türk, G; Demirci, E; Yüce, A; Sönmez, M; Özer, Ş; Aksu, Eh (My University, 2011)
The aim of this study was to determine the changes in diameter of corpus luteum (CL), maternal progesterone (P) concentration, lipid peroxidation and non-enzymatic antioxidant levels along with enzymatic antioxidant activities in pregnant ewes bearing single and twin foetuses. The ewes were selected from healthy animals that were brought to the abattoir for slaughtering. The ewes were divided into three groups: Group 1 (non-pregnant, non-oestrous, n = 30), Group 2 (pregnant bearing a single foetus, n = 30) and Group 3 (pregnant bearing twin foetuses, n = 12) after they were slaughtered. Pregnant ewes were in the first half of the pregnancy. The diameter of CL and P concentration of pregnant ewes bearing a single foetus or twin foetuses were found higher than that found in non-pregnant ewes. Similarly, the P concentration of pregnant ewes bearing twin foetuses was higher than that found in pregnant ewes bearing a single foetus. Malondialdehyde (MDA) level in pregnant ewes bearing twin foetuses was higher than that found in both non-pregnant and pregnant ewes bearing a single foetus. The serum glutathione (GSH) level and glutathione-peroxidase (GSH-Px) activity of pregnant ewes bearing twin foetuses were found lower than that found in non-pregnant ewes. Additionally, the GSH-Px activity of pregnant ewes bearing twin foetuses was found lower than that found in pregnant ewes bearing a single foetus. No significant difference was found between pregnant ewes bearing female and male foetus with respect to diameter of CL, P concentration and oxidative stress parameters. There were significant positive correlations between foetal number (0, 1, 2) and diameter of CL, P concentration, MDA level, and between P concentration and diameter of CL, MDA level. However, significant negative correlations were found between foetal number (0, 1, 2) and GSH level, GSH-Px activity, and between P concentration and GSH-Px activity. In conclusion, the diameter of CL enlarges, P production increases and oxidant ? antioxidant balance impairs because of the gestation stress in ewes during pregnancy.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Pregnancy Foetal number Corpus luteum Oxidative stress Progesterone Ewe